Učinkovitost energijskih pretvorb v hibridnih pogonskih sestavih - Katrašnik, Tomaž (Strojniški vestnik, 2007)
This paper presents a simulation and analytical analysis of the energy-conversion efficiency in parallel and series hybrid powertrains. The analytical approach is based on energy-balance equations, whereas the simulation approach is based on an accurate and fast forward-facing simulation model for simulating parallel and series hybrid powertrains. This combined simulation and analytical analysis provides a deep insight into the energy-conversion phenomena in hybrid powertrains and reveals the advantages and disadvantages of both hybrid concepts running under different operating conditions. From the presented results we concluded tha: 1) a parallel hybrid powertrain features better fuel economy than the series one for the applied test cycles, whereas both hybrid powertrain concepts have the best fuel economy during light-duty applications and 2) the electric conversion efficiency has a significant influence on the fuel-economy enhancement of hybrid powertrains.
Keywords: pogonski sistemi; energija; izkoristek; simulacija